The Photosynthetic Bacterium Rhodopseudomonas palustris Strain PS3 Exerts Plant Growth-Promoting Effects by Stimulating Nitrogen Uptake and Elevating Auxin Levels in Expanding Leaves - Hsu, Shu-Hua; Shen, Meng-Wei; Chen, Jen-Chih; Lur, Huu-Sheng; Liu, Chi-Te (Frontiers in Plant Science, 2021)
Rhodopseudomonas palustris strain PS3, a phototrophic bacterium, was originally isolated from a paddy field located in Taipei city, Taiwan, and showed positive effects on the growth of leafy vegetables. The aim of this study was to clarify the mechanism of the beneficial effects exerted by PS3 on plants. An ineffective R. palustris strain, YSC3, isolated from a paddy field located in Yilan County, was used as the negative control for comparative analyses. We cultivated nonheading Chinese cabbage (Brassica rapa var. chinensis) in 1/2 strength Hoagland hydroponic solution, in which nitrate is the main nitrogen source. We evaluated various plant physiological responses to inoculation with different bacterial inoculants. The N use efficiency (NUE) of PS3-inoculated plants was dramatically higher than that of YSC3-inoculated plants. The nitrate uptake efficiency (NUpE) was significantly elevated in plants treated with PS3; however, no excess nitrate accumulation was observed in leaves. We also noticed that the endogenous indole-3-acetic acid (IAA) levels as well as the cell division rate in the leaves of PS3-inoculated plants were significantly higher than those in the leaves of YSC3-inoculated plants. We examined the bacterial transcription of some genes during root colonization, and found that the expression level of IAA synthesis related gene MAO was almost the same between these two strains. It suggests that the elevated endogenous IAA in the PS3-inoculated plants was not directly derived from the exogenous IAA produced by this bacterium. Taken together, we deduced that PS3 inoculation could promote plant growth by enhancing nitrate uptake and stimulating the accumulation of endogenous auxin in young expanding leaves to increase the proliferation of leaf cells during leaf development.